State support programs for small and medium-sized enterprises in the Russian Federation - Campa, Antonio (Piccola Impresa / Small Business, 2017)
The following essay explains and analyses national programmes of support for small and medium enterprises, their modus operandi and results obtained in in the biggest nation of the World, namely the Russian Federation. That’s why, the reader has the possibility to know most popular national programmes currently in place, with particular attention not only about their structure but also about the logic and strategies that there are behind these plans. Moreover, in order to understand the correct functioning of the programs, the essay offers a general overview about the SME sector in Russia and main institutes that regulate the economic development and public strategies about SMEs in the Russian Federation.